SURFACE ELECTROMYOGRAPHY ASSESSMENT OF MASTICATORY MUSCLES RESPONSE TO CLEAR ALIGNER THERAPY: AN OBJECTIVE PRISMA STANDARDIZED SYSTEMATIC REVIEW - Amelia Anita Andreica; Diana Dudea; Alexandra Botoș (Romanian Journal of Oral Rehabilitation)
Aim of the study This systematic review aimed to centralize the information regarding the effect of the orthodontic treatment with clear aligners (CAT) on the masticatory muscles activity, functional or parafunctional, by objective recording means of surface electromyography (sEMG). Materials and methods : An electronic search was performed until June 2024 using the following search strategy :(((orthodontic OR clear OR removable) AND (aligner*)) OR Invisalign) AND (Bruxism OR (parafunctional masticatory forces) OR (masticatory muscle activity) OR clenching) AND (EMG OR Electromyography). Time restrictions for the search were established between 2000-2024.